PENGARUH UMPAN BALIK DAN INSENTIF TERHADAP PEMBERDAYAAN AUDITOR INTERNAL PEMERINTAH SERTA IMPLIKASINYA TERHADAP MOTIVASI DAN KINERJA - Ayu Fitaria Bangun; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of feedback and incentives for goverment internal auditor empowerment and its implications for their motivation and performance. This study used path analysis model. The samples are goverment internal auditor from Inspektorat Jenderal Kementerian Pekerjaan Umum in Jakarta. Collecting data conducted by the survey. There are 60 questioners distributed, and 41 of them are back which is submitted as the sample. The models analysis show that the value of goodness of fit model is 5,880 and CR value of all variables are between ±2,58. It means that models are fit to test. The results show that (1) feedback significantly gives positive influence to empowerment, (2) incentives significantly gives positive influence to empowerment , (3) empowerment significantly gives positive influence to motivation, (4) motivation significantly gives positive influence to internal auditor performance. This reseacrh result accept all the hypothesis with the significance 5%.